Study of Noise Propagation for Small Vessels - WERYK, Mateusz Wojciech; KOZACZKA, Eugeniusz; GRELOWSKA, Grażyna (Archives of Acoustics, 2015)
The paper presents the results of the noise propagation analysis in ship structures tested in a number of AHTS (Anchor Handling Tug Supply) vessels. Statistical Energy Analysis (SEA) based on numerical model developed specially for the purpose of this numerical investigation were conducted. This numerical model enabled the analysis of both the structural elements and the acoustic spaces. For the detailed studies 47 points fixed at various ship locations were selected. Prediction results with use of the numerical model were compared with the experimental results carried out in six identical AHTS vessels. Experimental studies were performed in accordance with the requirements of the International Maritime Organization (IMO) Resolution A.468 (XII). As a result one presented a comparison of the model analysis and experimental tests results.